Editorial Vol9 no2 - Alan Macquarrie (Scottish Journal of Residential Child Care)
In November 2008 the Child Care History Network held its inaugural conference at the Barns Conference and Study Centre at Toddington in Gloucestershire. The meeting was attended (among others) by three staff from the Scottish Institute for Residential Child Care. SIRCC has a warm interest in the work of the Child Care History Network and continues to be involved at various levels. I was privileged to attend the second annual conference of CCHN at the Barns Centre in November 2009. We have been fortunate in securing the publication of the main papers from this inspiring event, and these form the core of this issue of the Scottish Journal of Residential Child Care. We are most grateful to the speakers for revising their conference presentations for publication.